Peran Kepemimpinan Kepala Sekolah dalam Mewujudkan Merdeka Belajar di Sekolah Kristen - Atozanolo Lahagu; Dylmoon Hidayat (Universitas Kristen Satya Wacana, 2023)
Principal leadership has an essential role in advancing learning activities in schools. This study aims to determine the role of the principal's leadership in realizing the Freedom of Learning in Christian Schools. This study conducted a literature study to collect materials from books, journals, articles, and other sources related to school principals' leadership in realizing Independent Learning in Christian schools. The results of the study indicate that the principal's leadership role is (1) Responsible for teaching, encouraging, and directing the school community, (2) Planning, mobilizing, coordinating, and synchronizing all school resources, (3) Providing support in the implementation of the independent program of activities. Learning by preparing, financing, and documenting, (4) Creating a conducive school organizational culture, (5) Providing motivation, and (6) Carrying out various supervision and control.